Features of the flow of concentrated suspensions of solid particles - Skul’skiy, Oleg Ivanovich (Computational Continuum Mechanics, 2021)
Concentrated suspensions of solids, widely used in the pharmaceutical, cosmetic and food industries, exhibit complex rheology. In the rheometric one-dimensional flows of concentrated suspensions, a smooth or abrupt increase in stresses with a smooth increase in the strain rate intensity can be observed. This is related to the appearance of a first-order phase transition. In our previous work, a phenomenological rheological model of a concentrated suspension of solid particles in a Newtonian dispersion liquid has been developed. This model is characterized by an S-shaped flow curve and describes both continuous and abrupt increases in the stress intensity with a uniform increase in the strain rate intensity. In this work, exact analytical formulas are obtained for the flow velocity profiles of suspensions measured using rotary viscometers. The model proposed before is modified to take into account the non-Newtonian properties of the dispersion medium, which demonstrates pseudoplastic properties at low stress intensities and dilatant properties at high stress intensities. Based on the developed numerical model, the features of the flow of highly concentrated suspensions in plane and axisymmetric channels are analyzed. It is shown that in a flat diffuser, in contrast to Newtonian and pseudoplastic fluids, the longitudinal velocity of the suspension slows down near the walls, where the stresses are maximum, and accelerates in the central part of the channel. Calculations for the submerged jet in the area bounded by the walls show that, with an increase in the average velocity of the incoming pure liquid by more than 0.01 m/s, there occurs a local velocity vortex bounded by a layer with high particle concentration and more viscous medium; particle concentration inside the vortex is minimum.
Keywords: highly concentrated suspensions; rheological model; non-Newtonian dispersion medium; diffusion-convective transfer; numerical solution; plane and axisymmetric flows